The Literary Characteristics and Innovative Design of Chinese Taoist Graphic Arts - xiao, liyao (Pacific International Journal, 2023)
Taoism is the purest native religious sect in China, and one of the most representative aspects of Taoist culture is graphic art. In this paper, we trace and analyze the origin of Taoist culture and art, and summarize its characteristics; from the aesthetic perspective, we classify Taoist graphic art by subject matter, analyze the classic patterns of Taoist graphics, and summarize their artistic meanings and connotations, and then express the aesthetic implications of Taoist graphics; from the perspective of the development and use of graphics, we first analyze the use of Taoist graphics in modern clothing, and propose the concept of pattern From the perspective of the development and application of graphics, we first analyze the use of Taoist graphics in modern clothing, and put forward the concept of secondary design for traditional Taoist graphics, and then make creative use of pattern design in clothing design.